2017
DOI: 10.1001/jama.2017.11750
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Studies Help Clarify the Complexities of Lipid Biology and Treatment

Abstract: A randomized controlled trial of laparoscopic Nissen fundoplication versus proton pump inhibitors for the treatment of patients with chronic gastroesophageal reflux disease (GERD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…This observation contrasts with findings from Mendelian randomisation studies which showed that having a lower LDLc associated with PCSK9 variants was linked to increased risk of diabetes in a manner similar to that seen for variation in the gene for 3-hydroxy-3methyl-glutaryl co-enzyme A (mimicking statin therapy) (40). This discordancy between genotypicand clinical trial -findings reflects the strengths and weaknesses of each approach to determining the benefits and disadvantages on an intervention (see (41) for a review). As noted, the duration of FOURIER at just over 2 years limits the ability to detect late-appearing treatment-emergent side effects, and the genetic observations leave the diabetes link an open question.…”
Section: Clinical Trial Evidence For the Benefits Of Profound Ldl Cholesterol Loweringmentioning
confidence: 80%
“…This observation contrasts with findings from Mendelian randomisation studies which showed that having a lower LDLc associated with PCSK9 variants was linked to increased risk of diabetes in a manner similar to that seen for variation in the gene for 3-hydroxy-3methyl-glutaryl co-enzyme A (mimicking statin therapy) (40). This discordancy between genotypicand clinical trial -findings reflects the strengths and weaknesses of each approach to determining the benefits and disadvantages on an intervention (see (41) for a review). As noted, the duration of FOURIER at just over 2 years limits the ability to detect late-appearing treatment-emergent side effects, and the genetic observations leave the diabetes link an open question.…”
Section: Clinical Trial Evidence For the Benefits Of Profound Ldl Cholesterol Loweringmentioning
confidence: 80%
“…Up to a 130% increase in HDL-C and a 40% decrease in LDL-C (calculated using the Friedewald formula) were observed in phase 3 trials with four different CETP inhibitors, the trial populations of which consisted predominantly of individuals with documented atherosclerotic cardiovascular disease (ASCVD). Note, however, that the reductions in LDL-C, calculated in most CETP trials by the Friedewald equation, more than likely overestimated the extent of LDL-C lowering [8,9]. Overestimation of LDL-C reductions holds particularly true at lower LDL-C levels, as in those patients recruited in the phase 3 CETP inhibitor trials, who were on statin therapy during the trials [9].…”
mentioning
confidence: 99%
“…Note, however, that the reductions in LDL-C, calculated in most CETP trials by the Friedewald equation, more than likely overestimated the extent of LDL-C lowering [8,9]. Overestimation of LDL-C reductions holds particularly true at lower LDL-C levels, as in those patients recruited in the phase 3 CETP inhibitor trials, who were on statin therapy during the trials [9]. LDL-C reductions of up to 20%, determined in later trials by beta quantification, more accurately reflect LDL-C lowering achieved with the addition of CETP inhibitors to statin therapy, and are in effect a proxy for the extent of apoB lowering produced, which is a more accurate predictor of CVD outcomes [8,10].…”
mentioning
confidence: 99%
See 1 more Smart Citation